2021
DOI: 10.3389/feduc.2021.761485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of School Closures Resulting From COVID-19 in Autistic and Neurotypical Children

Abstract: The purpose of this study was to assess differences in negative consequences resulting from pandemic-related school closures between autistic and neurotypical children. We predicted that more negative consequences overall would be reported for children with autism compared to neurotypical children. We also expected to observe differences in the types of stressors reported between these two groups, with disruptions to daily routines more commonly reported for children with autism and stress due to social isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 31 publications
1
26
0
4
Order By: Relevance
“…Instead, the positive benefit of school attendance on CYP’s MH does not appear to extend to CYP experiencing SD, and indeed, to many autistic CYP, including those who do not show any obvious school distress. Interestingly, research comparing the effects of the Covid-19 related school closures on autistic and neurotypical CYP has found that whilst parents of autistic CYP reported greater negative changes in their children as a consequence of the school closures, and greater negative emotions at the initial peak of the school closures relative to the parents of neurotypical peers (with the loss of daily structure and uncertainty highlighted as key factors), they also reported significantly more positive changes and marginally more positive emotions in their children (such as them feeling relaxed, hopeful, and confident about the future) when compared to the parents of neurotypical children (140). Hence, whilst there is complexity here, and a clear negative impact of unexpected, profound change to daily routine, the impact of the school environment itself on autistic CYP’s mental health does not appear to be equivalent to that derived by neurotypical CYP, and may instead be damaging for some autistic CYP.…”
Section: Discussionmentioning
confidence: 98%
“…Instead, the positive benefit of school attendance on CYP’s MH does not appear to extend to CYP experiencing SD, and indeed, to many autistic CYP, including those who do not show any obvious school distress. Interestingly, research comparing the effects of the Covid-19 related school closures on autistic and neurotypical CYP has found that whilst parents of autistic CYP reported greater negative changes in their children as a consequence of the school closures, and greater negative emotions at the initial peak of the school closures relative to the parents of neurotypical peers (with the loss of daily structure and uncertainty highlighted as key factors), they also reported significantly more positive changes and marginally more positive emotions in their children (such as them feeling relaxed, hopeful, and confident about the future) when compared to the parents of neurotypical children (140). Hence, whilst there is complexity here, and a clear negative impact of unexpected, profound change to daily routine, the impact of the school environment itself on autistic CYP’s mental health does not appear to be equivalent to that derived by neurotypical CYP, and may instead be damaging for some autistic CYP.…”
Section: Discussionmentioning
confidence: 98%
“…During lockdown, many psychologists and therapy sessions moved online. However, while telehealth was positive for some, it proved problematic for people with ASD [13].…”
Section: Discussionmentioning
confidence: 99%
“…For example, many children with ASD insist on sameness in their routines, but the shifting to online schooling created some distress for children who were not used to these new changes (Ameis et al, 2020). These added stressors have also been found to impact other behaviors associated with ASD, such as an increase in behavioral meltdowns, sensory issues, and self-stimming behaviors (Genova et al, 2021). Given these challenges faced by both caregivers and children with ASD, it is important to examine ASD and other IDD groups separately, and in comparison to each other.…”
Section: Covid-19 Impact On the Intellectual And Developmental Disabi...mentioning
confidence: 99%